Didactic Testing of Students with Special Course «Disadaptation of Preschoolers and its Consequences» (Based on the Stating Experiment) - Zdanievych, Larysa (Pedagogical Discourse, 2013)
The author reveals theoretical approaches on the problem under research, interprets the views of different researchers. She acquaints with various approaches as for determination of the notion «test», «didactic test» and their classifications, peculiarities of making tests of the closed form and their components for the students-bachelors on speciality «Pre-School Education», basic traditional forms of test tasks, principles of construction of the answer. The author describes main rules, which must be followed in the process of forming tasks for those who will be tested. She offers the results of her own research, which prove topicality and practical necessity of research of some questions.